Radiology Comprehensive Review of AI-Driven Imaging Technologies and their Impact on Diagnostic Accuracy - Alrashdi, Ahmed Aiah Abdullah; Alrasheedi, Afrah Manwer Eieed; Alazmi, Norah Fahhad G; Algharbi, Adel Abdullah Bakheet; Alanazi, Khalid Sihman Dhahir; Alshammari, Hadeel Obaid Saleh; Alshammari, Dalal Hamdan Saleh; Alshammari, Homoud Tulayhan Mubarak; Aldubl, Ibrahim Saud Salh; Alharbi, Ayed Hameed (Journal of Ecohumanism, 2024)
Radiology has also received the double-edged gift of artificial intelligence (AI) that accelerates the speed and efficiency of diagnosis. This systematic review aims to present the outcome of AI-assisted imaging, from accuracy examinations to advancing radiology work processes. It looks at different AIs using algorithms in imaging techniques like X-rays, CT scans, MRI, and ultrasounds. AI can benefit radiologists by enhancing results in detecting diseases, including cancers, cardiovascular diseases, and neurological disorders. Still, some barriers to adoption, data quality, and ethical issues have not been addressed. This review addresses these concerns while also considering how AI may enhance patient outcomes and radiology operations.